Association of Large Vessel Aneurysm/Pseudo-Aneurysm/Aortitis and Deep Vein Thrombosis in Patients with Behçet’s Disease: A Case Report - Shenavandeh, Saeedeh; Johari, Hamed G.; Aflaki, Elham (Current Rheumatology Reviews, 2022)
Background: Behçet’s disease (BD) is a complex vasculitis with some vascular manifestations including venous thrombosis, arterial thrombosis/aneurysm/pseudoaneurysm, and co-associated venous thrombosis and arterial lesions. We present two patients with Behçet’s disease came with progressive both arterial and venous involvement. Case Presentation: The first patient was a young man with recurrent oral aphthosis and skin folliculitis and referred with complaint of new abdominal pain and 2 months severe headache. He had not referred to a physician due to COVID-19 pandemic until that time. In addition, he gradually developed a lower extremity edema and eventually was diagnosed with BD complicated with brain sagittal sinus vein thrombosis, abdominal aortic aneurysms and aortitis and deep vein thrombosis (DVT) of femoral vein. The second patient was a young woman with previous history of uveitis, DVT and recurrent oral and genital aphthosis presented with a large inguinal mass due to large iliac artery pseudoaneurysm impending to rupture, and after the operation, due to poor follow-up, developed a new femoral DVT. Conclusion: It seems the same inflammatory process is responsible for arterial and venous involvement in patients with BD, so it should be considered that involvement in one side (venous/arterial) can be a risk factor for the other side (venous/arterial) and early immunosuppressive treatment should always be considered to improve the prognosis.
Keywords: pseudo-aneurysm